The establishment of metadatabase: The program Euromarsin for the marin sediments samples - ΠΕΡΙΣΟΡΑΤΗΣ Κ.; ΑΝΔΡΙΝΟΠΟΥΛΟΣ Α.; ΖΗΜΙΑΝΙΤΗΣ Ε.; ΖΑΧΑΡΑΚΗ Π. (Bulletin of the Geological Society of Greece, 2018)
The project EUMARSIN (European MARine Sediment Information Network), is an international scientific project financed by the European Community and its aim has been the development of an internet retrievable metadatabase containing the marine sediment samples collected from the European Seas. The project, with duration of two years, started on November 1998 and ended on October 2000. This paper elucidates the concerted activities of the partners participating in the project and represent the Marine Geology Departments of the Eurogeosurveys (ERG) now called Geological Survey Organizations (GSOs) of the European Union maritime countries, with the additional participation of a private company specialized on marine data management. The metadata can be accessed on the EU-SEASED Website through both an alphanumeric search and retrieval interface and by a geographical interface which allows the user to define an area of interest on a scrollable map showing the distribution of the seafloor sample/core locations. The EUMARSIN metadatabase now contains approximately 180.000 seabed samples collected by the Geological Surveys and other research organizations, universities, hydrographie offices and commercial companies in Europe. The metadatabase will be regularly updated by the partners on an on-line data entry system which will allow other organizations to contribute their metadata either retrospectively or as new data. The outcome of the EUMARSIN project, will be the successful establishment of the http://www.eu-seased.net marine sediment metadatabase and the development of analogous databases in each Geological Institute with the same specifications. This constitutes the first pan-European metadatabase in the marine geoscience field.